(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
In the Philippine basic education system, where the medium of instruction shifts to the mother tongue in public kindergarten up to grade 3, the implications for future educators require exploration. This study aimed to evaluate the proficiency of pre-service elementary teachers in the Ilokano language within the educational landscape of La Union. The objective was to assess their readiness to implement the Mother-Tongue Based - Multilingual Education (MTB-MLE) curriculum. Employing a descriptive-correlational research design, the study encompassed pre-service elementary teachers across various state colleges, universities, and private higher education institutions in the province. Quantitative analysis techniques were employed to dissect the data, encompassing frequency counts and percentages for demographic variables alongside Pearson’s correlation coefficient for relevant linguistic assessments. The outcomes illustrated that most respondents identified as female and hailed Ilokano as their primary language in their home environments. However, their proficiency in the Ilokano language, particularly in terms of mechanics, grammar, organization, and content, was observed to be at a developing stage. This implies that while the pre-service elementary teachers possessed some level of competency in these language aspects, there was room for improvement and growth. Their grasp of the finer points of language mechanics, such as punctuation and syntax, as well as their understanding of grammar rules, organization of ideas, and depth of content expression, appeared to be progressing. In other words, their skills and abilities in these language dimensions still needed to be fully mature or advanced, suggesting that there was still space for enhancement through focused learning and training. This developmental stage signifies that they had a foundation to build upon but would benefit from targeted interventions and educational efforts to refine and elevate their language proficiency to a more proficient level. Despite considering factors such as age, gender, enrolled course, school type, ethnolinguistic background, and primary language spoken at home, the study demonstrated that these variables, except for the course of study, did not significantly influence the pre-service teachers’ grammar and content competencies. Intriguingly, the course they were enrolled in markedly influenced their mechanics and organizational competencies. The study’s implications underline the necessity for an Ilokano teaching capacity program to augment and enrich both linguistic and pedagogical skills among pre-service educators, ensuring more effective implementation of the MTB-MLE curriculum. This advances teachers’ proficiency and aligns with the broader goals of enhancing the quality of mother tongue-based education in the Philippines.